PERANAN APARAT PENEGAK HUKUM DALAM PENCEGAHAN KEJAHATAN DI BIDANG PERTANAHAN - Hafiz Sutrisno; Novi Maimory, Aminoel Akbar (Pahlawan Tuanku Tambusai University, 2024)
Indonesia is a country dominated by land, water, and sovereign land, in Indonesia land has multiple values, so the term homeland and homeland is used by the Indonesian people to refer to the country's territory by describing the area dominated by land, water, and sovereign land. In exercising these rights, it is not uncommon to cause various problems or disputes related to land. Land disputes occur because land has an important position that can prove the independence and sovereignty of its owner. Until now, there are still lands that do not have proof of land rights because they are inherited from customary law or land rights according to colonial law, thus causing their own problems and every year land disputes tend to increase, both in urban and rural areas. To answer this, the government realizes the hopes of the community by forming a land regulation which is stated in Law No. 5 of 1960 concerning Basic Agrarian Principles. To obtain a land certificate, the land must first be registered with the National Land Agency of the City/Regency by attaching complete administrative documents. To carry out land registration, a person is usually accompanied by a notary so that the registrant does not make a mistake in registering his land. In reality, law enforcement efforts to prevent forgery of land certificates have not yet succeeded. Keywords: Law Enforcement, Crime, Land.